Frequency and habits of cigarette smoking among adolescents - Piotr Kozłowski; Magdalena Kozłowska; Karolina Kozłowska (Kazimierz Wielki University, 2017)
The aim of the study was to evaluate the habits and frequency of cigarette smoking. The study included 112 participants. In the study group, 67,64% of respondents were females whereas 32,36% were males. The age of participants ranged from 15 to 26 years. The study conducted in the period from January 2017 to February 2017 and it employed standardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 16 questions single-choice or multiple- choice questions. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. In the study group 28.8% of respondents answered that they smoked cigarettes in the past, while smoking a cigarette at the moment declared by 12.6% of people. Half of the respondents smoked about 10 cigarettes a day. Over 60% of respondents declared to start smoking over 18 years of age. More than 30% of respondents smoked e-cigarettes. Almost 100% of the respondents aware of the dangers of smoking. Over ¾ respondents have ever tried to break up with addiction. The respondents were asked where they most often they smoke cigarettes. Nearly half (46.9%) of the respondents choose a public place as the place where cigarettes are most commonly smoked (work, school). Nearly half of the respondents (46.9%) indicated that at least one parent in the household smokes cigarettes. However, only 9.74% of respondents said they smoked cigarettes at home with the company of a family. The question "What prompted you to first try a cigarette?" The most common answer was the "curiosity" and "friends suggestion" (78,1%). As many as 46.9% of respondents say that stress increases the number of smoked cigarettes.